Fault-tolerant control of hypersonic vehicles based on fast fault observer under actuator gain loss fault or stuck fault. (9th August 2020) - Zhu, P.; Jiang, J.; Yu, C.
ABSTRACT: This paper proposes a fault-tolerant control (FTC) method based on fast fault observer (FFO) to solve the problem of actuator gain loss fault and stuck fault for hypersonic vehicles. Firstly, an input-output feedback linearisation model is presented that considers parametric uncertainties, control input saturation, disturbances and actuator faults. Secondly, the above factors are defined as an integrated fault item, and an improved fast fault observer is designed to estimate the integrated fault in real time. Finally, the fault-tolerant controller is constructed based on the sliding mode and fault estimation. In case of unknown faults, the effects of gain loss fault or stuck fault happen on elevators and the engine can be quickly processed, Also, the asymptotically stable tracking of the flight output reference command is completed to achieve fault-tolerant control. The final simulation experiment verifies the effectiveness of the proposed method.